2018
DOI: 10.17981/econcuc.39.2.2018.04
|View full text |Cite
|
Sign up to set email alerts
|

Modelo explicativo de la rentabilidad económica del cultivo de durazno en la provincia de Pamplona, Colombia

Abstract: En Colombia, el departamento de Norte de Santander, en el cual se ubica la Provincia de Pamplona, es el segundo mayor productor de durazno del país posicionándose como un cultivador de vocación frutícola. El objetivo de esta investigación fue determinar un modelo econométrico explicativo de la rentabilidad económica para veintisiete fincas productoras de durazno con la finalidad de evaluar cómo las variables costo de producción, rendimiento, ingresos y edad del cultivo afectan la rentabilidad económica de esto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
1
2
0
5
Order By: Relevance
“…As a result, according to the proposed econometric it is evident that, with respect to the explanatory variables, their estimated coefficients were significantly different from zero at a 5% significance level, consistent with hypothesized signs and, as expected, production cost was negatively related to economic profitability, and P, Q and TR presented a positive relationship. These findings confirm those of Flórez and Miranda (2017) and Cancino, Cancino-Escalante and Quevedo-García (2018) who in their studies identified that, for crops such as camu camu and peach, production costs also presented a negative impact on profitability suggesting therefore, that farmers should focus on cost reduction strategies through, for example, innovative practices. Furthermore, it can be argued that the model passed all statistic diagnostic checks where the ADF, PP and the KPSS tests indicated the presence of stationarity.…”
Section: Discussionsupporting
confidence: 84%
“…As a result, according to the proposed econometric it is evident that, with respect to the explanatory variables, their estimated coefficients were significantly different from zero at a 5% significance level, consistent with hypothesized signs and, as expected, production cost was negatively related to economic profitability, and P, Q and TR presented a positive relationship. These findings confirm those of Flórez and Miranda (2017) and Cancino, Cancino-Escalante and Quevedo-García (2018) who in their studies identified that, for crops such as camu camu and peach, production costs also presented a negative impact on profitability suggesting therefore, that farmers should focus on cost reduction strategies through, for example, innovative practices. Furthermore, it can be argued that the model passed all statistic diagnostic checks where the ADF, PP and the KPSS tests indicated the presence of stationarity.…”
Section: Discussionsupporting
confidence: 84%
“…Even though there are many studies on the biological and agricultural aspects of blackberry production, forecast analysis has received very little attention in the literature, most probably because in many countries the data on the quantity of production is inaccurate or lacking (Cancino, Cancino & Cancino, 2021). Nonetheless, this methodology has been widely employed in other fruit crops to forecast production, consumption, imports and exports.…”
Section: Literature Reviewmentioning
confidence: 99%
“…La formalización del modelo econométrico que aquí se propone, se fundamenta en el planteado por [27] y [28], con algunas modificaciones. En este sentido, el modelo propuesto se basa en el método de los mínimos cuadrados ordinarios (MCO) expresado por la ecuación que se presenta a continuación 3 β2 = Coeficiente asociado a los costos de producción agrícola (CPA).…”
Section: B) Especificación Del Modelo Econométricounclassified
“…No obstante, indicadores como la rentabilidad económica han sido ampliamente empleados, tal es el caso de los trabajos de [24], cuyo objetivo fue analizar la influencia del rendimiento, edad del cultivo y densidad de siembra sobre la rentabilidad económica del cultivo de camu camu. Asimismo, [25] calcularon la rentabilidad económica de la producción de jitomate bajo condiciones de invernadero; [26] examinaron la rentabilidad económica del cultivo de la mandioca por medio del costo de producción y el ingreso; [27] determinaron a través de un modelo econométrico, cómo los costos de producción, rendimiento, ingresos y edad del cultivo afectan la rentabilidad económica del cultivo de durazno. Finalmente [28], propusieron un método para evaluar la rentabilidad económica de los cereales alto andinos en Perú.…”
unclassified